2006
DOI: 10.1080/10942910600596571
|View full text |Cite
|
Sign up to set email alerts
|

Linear Viscoelastic Properties of Regular- and Reduced-Fat Pasteurized Process Cheese During Heating and Cooling

Abstract: The rheology of process cheese during heating and cooling was examined by measuring the transient and dynamic linear viscoelastic properties of regular fat, lower moisture and an 80% reduced-fat, higher moisture pasteurized process cheese from 10 to 50°C. The dynamic (stress and frequency sweep) and transient (creep and recovery) rheological properties of the reduced-fat process cheese were found to be higher than that of regular-fat process cheese, indicating that fat content changed rheological properties mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 29 publications
9
32
0
1
Order By: Relevance
“…This is due to the action of fat as a lubricant. Similar observation has been reported by Subramanian et al (2006) who concluded that fat reduction results in increased viscoelastic properties in processed cheese. The softening effect of fat on the texture of processed cheese generally has also been observed using other methods (Dimitreli & Thomareis, 2007;Green et al, 1986;Stampanoni & Noble, 1991).…”
Section: Frequency (Hz)supporting
confidence: 86%
See 2 more Smart Citations
“…This is due to the action of fat as a lubricant. Similar observation has been reported by Subramanian et al (2006) who concluded that fat reduction results in increased viscoelastic properties in processed cheese. The softening effect of fat on the texture of processed cheese generally has also been observed using other methods (Dimitreli & Thomareis, 2007;Green et al, 1986;Stampanoni & Noble, 1991).…”
Section: Frequency (Hz)supporting
confidence: 86%
“…For the evaluation of the viscoelastic behavior of processed cheese and the way that it is affected by different factors, dynamic rheology has mainly been used (Bowland & Foegeding, 2001;Joshi et al, 2004;Lee & Klostermeyer, 2001;Lee, Anema, & Klostermeyer, 2004;Marchesseau, Gastaldi, Lagaude, & Cuq, 1997;Pereira et al, 2001;Piska & Š te tina, 2004;Subramanian, Muthukumarappan, & Gunasekaran, 2006;Sutheerawattananonda & Bastian, 1998). Some of these researchers have studied the effect of chemical composition on the viscoelastic properties of processed cheese.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear regression was used to determine the corresponding parameters of power-law equation. Nonlinear regression analysis was conducted to obtain the parameters of five Maxwell elements, using the procedure proposed by Subramanian et al [20]. Multiple regression analysis was applied in order to establish the relationships between rheological parameters and physicochemical properties.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of the viscoelastic behavior of processed cheese and the way that it is affected by different factors, dynamic rheology has mainly been used [6]. Moisture acted as a plasticizer and fat as a lubricant both contributing to a more liquid-like behavior of the samples.…”
Section: Introductionmentioning
confidence: 99%